Kerja Shift Pagi, Sore Dan Malam Dengan Kelelahan Pada Perawat Wanita Di Ruang Rawat Inap RSUD Dr. R. Goeteng Taroenadibrata Purbalingga - Tri Sumarni; Pramesti Dewi (Viva Medika, 2014)
Shift work is work scheduled, either fixed or not fixed or outside normal hours of work. Each shift system has advantages and disadvantages. Shift systems can result in fatigue, health,social life and work performance. Woman nurses easy to feel less tired when working in shifts. Fatigue during work consist of physiological and psychological fatigue. Purpose of this study was to determine differences in the level of fatigue between morning,evening and night shift. The study was conducted in Inpatient Room dr. R. Goeteng TaroenadibrataRegional General Hospital. The study was analytical observation with cross sectional approach. Sampling waspurposive sampling and using a questionnaire as a data collection tool that was distributed to 90respondents. The statistical analysis used chi square test. The result of this study shows that therewere significant difference between the working fatigue on woman nurses, where p value 0.043. Key word : fatigue, shiftwork, woman nurse